The Relationship between Management Responsibility, Service Quality Accountability, and the Effectiveness of the Quality Assurance System at Jabal Ghafur University - Boihaki Boihaki; Teuku Isnaini; Cut Yusnidar; Fuad Fuad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The objectives of this research were to describe the effectiveness of quality assurance system at Jabal Ghafur University and to find the relationship between management responsibility, service quality accountability, and team performance with the effectiveness of quality assurance system at Jabal Ghafur University. This current research employed qualitative approach, x post facto research category of correlative description. The population of this research was permanent lecturers at Jabal Ghafur University. As many as 150 samples were taken from the population by using proportional cluster sampling technique. The data were collected by using questionnaire and were further analyzed by employing Structural Equation modeling (SEM) on Partial Least Square (PLS) software. The results of the research showed that (1) the effectiveness of quality assurance system, service quality accountability, and management responsibility fell into the average category of good, (2) the higher team performance was not followed by the more effective quality assurance system.